Rural women farmers participation in planning and implementation of agricultural practices in North Eastern Nigeria - Umar, Abdulmumini; Man, Norsida; Mohd Haris, Nur Bahiah; Kamarulzaman, Nitty Hirawaty (African Journals Online (AJOL), 2022)
The study investigated participation of women farmers in planning and implementation of agricultural practices in northeastern Nigeria. Multistage sampling procedure was used to select 378 respondents out of 6758 women farmers in the zone. Questionnaire was used to collect data from the sampled farmers. Mean and standard deviation were used for analyses of data. The study showed low level of women farmers participation in planning agricultural practices ((x bar = 2.27)). Implementation of agricultural practices among women farmers had high-level participation ((x bar = 3.74)). The need for extension programme that would ensure effective motivation by extension workers for meaningful participation of women farmers in planning and implementation of agricultural practices become necessary for increase productivity.